Prefixes of the Fibonacci word that end with a cube - Rampersad, Narad (Comptes Rendus. Mathématique)
The Fibonacci word $f = 010010100100101… $ is one of the most well-studied words in the area of combinatorics on words. It is not periodic, but nevertheless contains many highly periodic factors (contiguous subwords). For example, it contains many cubes (i.e., non-empty words of the form $xxx$). We study the prefixes of the Fibonacci word that end with a cube. Using the computer prover Walnut, we obtain an exact description of the positions of the Fibonacci word at which a cube ends. This gives a certain measure of how close the Fibonacci word is to being periodic.